Solidarność Nauczycielska . pismo pracowników oświaty, no. 42, 1985 - Region Środkowo-Wschodni NSZZ "Solidarność", [auxiliary ed. committee] (NSZZ "Solidarność" Region Środkowo-Wschodni, 1985)
Print run: 500-1000 copies